College Expectations for All? The Early Adult Outcomes of Low-Achieving Adolescents Who Expect to Earn a Bachelor's Degree. Issue 2 (2nd April 2016) - Martin, Anne; Gardner, Margo
Abstract : Critics of the college-for-all ethos argue that it encourages low-achieving adolescents to develop unrealistically high expectations. This argument posits that low-achievers waste time and money, and risk disappointment and self-recrimination, pursuing college when they are unlikely to complete it. The present study uses two national data sets—Add Health and the National Longitudinal Survey of Youth 1979—to test the proposition that expecting to earn a bachelor's degree (BA) puts low-achieving students at risk of disadvantageous early adult outcomes. Youth reported their educational expectations in high school, and their income-to-needs ratios and depressive symptoms were measured approximately a decade later. Results in both data sets suggest that the expectation of a BA was advantageous for all students, regardless of achievement level. Low-achievers who expected to earn a BA had higher educational attainment, higher income-to-needs ratios, and fewer depressive symptoms than low-achievers who did not expect to earn a BA.